2015
DOI: 10.2217/pgs.15.138
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Combined CYP3A4 and CYP3A5 Single-Nucleotide Polymorphisms on Tacrolimus Exposure in Kidney Transplant Recipients: A Study According to the Post-Transplant Phase

Abstract: Our data support a critical role of the CYP3A5 6986A>G and CYP3A4 -392A>G polymorphisms on the variation of Tac exposure during the early and the late PT phase, respectively. The establishment of customized Tac doses, according to CYP3A4/CYP3A5 genotype combination and the PT time, may allow preventing graft rejection and improving the safety profile of this drug. Further studies are needed to investigate this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 26 publications
4
20
0
Order By: Relevance
“…Several studies have been conducted in North Africans in order to evaluate the effect of CYP3A5 variants on tacrolimus dosage and on tacrolimus blood concentrations normalized by the dose and proved that there is significant difference between renal transplant patients with the CYP3A5*1 allele compared to homozygotes for the CYP3A5*3 allele, especially during the early post-transplant phase ( Elmachad et al., 2012 ; Aouam et al., 2015 ). To our knowledge, this is the first study to examine the association of the CYP3A5*3 allele with tacrolimus dose requirements and C/D ratios in Egyptian kidney transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been conducted in North Africans in order to evaluate the effect of CYP3A5 variants on tacrolimus dosage and on tacrolimus blood concentrations normalized by the dose and proved that there is significant difference between renal transplant patients with the CYP3A5*1 allele compared to homozygotes for the CYP3A5*3 allele, especially during the early post-transplant phase ( Elmachad et al., 2012 ; Aouam et al., 2015 ). To our knowledge, this is the first study to examine the association of the CYP3A5*3 allele with tacrolimus dose requirements and C/D ratios in Egyptian kidney transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies published in other North African populations (Algerians, Morocco, Tunisians, Libyans) showed that the CYP3A5*3 allele was the most prevalent with a frequency that reaches even 90% (Novillo et al, 2015;Fernańdez-Santander et al, 2016), whereas in the African population as a whole is observed great diversity from 4 to 95% (Zhou et al, 2017). Several studies have been conducted in North Africans in order to evaluate the effect of CYP3A5 variants on tacrolimus dosage and on tacrolimus blood concentrations normalized by the dose and proved that there is significant difference between renal transplant patients with the CYP3A5*1 allele compared to homozygotes for the CYP3A5*3 allele, especially during the early post-transplant phase (Elmachad et al, 2012;Aouam et al, 2015). To our knowledge, this is the first study to examine the association of the CYP3A5*3 allele with tacrolimus dose requirements and C/D ratios in Egyptian kidney transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with the fact that CYP3A4 existed mostly in the gastrointestinal tract of the recipient and CYP3A5 presented mainly in the liver of the donor, both being sites of drug metabolism. Almost all studies had reported a lower Tac exposure and/or a higher dose requirement in individuals who were CYP3A5 expressors (harboring CYP3A5 *3 AA or AG genotype) than that in nonexpressors ( CYP3A5 *3 GG genotype ) [ 34 ]. Besides, Qiu XY et al observed in their study performed in 103 renal transplant recipients that the CYP3A4*1G AA genotype was found to have a lower dose-adjusted concentration [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In these patients, the CYP3A5 *3 polymorphism was associated with rapid worsening of hepatic damage, but CYP3A4 *1 carriers showed only a small effect. The findings therefore suggested that the CYP3A5 *3 variant that determines decreased CYP3A5 enzymatic activity[33] could influence hepatic and renal exposure to sorafenib, with severe associated damage.…”
Section: Pharmacogenetics Of Approved Drugsmentioning
confidence: 99%